The impact of UX work on communication and collaboration in software startups - Saad, Jullia; Choma, Joelma; Alvaro, Alexandre; Zaina, Luciana (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2023)
Software startups are companies that operate under constant time and business pressures and often teams have problems on communication and collaboration. However, little has been discussed about these problems in the literature. Startup professionals have recognized user experience as an important software quality. This paper presents an investigation about the impact of UX work on team communication and collaboration in startups. We conducted a qualitative study with two startups in Brazil and found out six categories of UX work issues. Our work contributes by discussing the impact of these issues on team communication and collaboration which are related to team composition, tools adopted and organization culture.